Profil Hematologi Mencit Pasca Pemberian Jamu Temulawak Secara Oral (HEMATOLOGICAL PROFILE IN MICE WITH ORAL ADMINISTRATION OF JAMU TEMULAWAK) - Septianto, Robby Deddy; Ardana, Ida Bagus Komang; Sudira, I Wayan; Darmayudha, Anak Agung Gde Oka (Buletin Veteriner Udayana, 2015)
The purpose of this study to assess changes in hematological profile (leucocyte differential,total leukocytes and platelets) mice with oral administration of jamu temulawak. 25 male miceaged 12 weeks, each weighing 30 g were divided into five groups and five replications. P0 suchdoses given as a control (0 mg/100 g), P1 (10 mg/100 g), P2 (20 mg/100 g), P3 (30 mg/100 g), andP4 (40 mg/100 g). Differential leukocytes, total leukocytes and platelets of mice, using the SysmexHematology analyzer showed oral administration of jamu temulawak was highly significant  to total leukocytes and significantly  on lymphocytes of mice, whereas the total platelets, eosinophils,neutrophils, basophils and monocytes showed no significant difference, but the effect is happeningis within normal limits. Thus giving jamu temulawak can be used to maintain animal healthassociated with hematologic profiles.
Keywords: curcuma xanthorriza roxb; hematology; differential leukocyte; total leukocytes; platelets